Meaning and Forms of Muhammadiyah Citizens' Spirituality during the Covid 19 Pandemic in a Sociological Perspective - Muhammad Junaedi; Fajar Muharram; Hendra Sukmana (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
This study aims to understand the meaning and spirituality of Muhammadiyah residents, especially in the Sidoarjo area during the Covid 19 pandemic. This study uses a qualitative descriptive method with a phenomenological approach. Data were collected by observing, documenting and interviewing leaders, medical personnel and Muhammadiyah residents in the Sidoarjo area. The results showed that the meaning of spirituality during the Covid-19 pandemic was a reflection of strengthening and planting religious values in life as a basic framework for strengthening faith. In the face of the Covid 19 Virus Pandemic, the practice of spiritual values does not only contain human relations to God alone, but requires a balance between scientific-oriented-based medical strengthening and faith in Allah SWT. The form of spirituality in strengthening faith for Muhammadiyah members is reflected in the social responsibility of humanity. This form of spirituality is embedded in the spirit of Al Maun's social theology by carrying out humanitarian jihad through the Muhammadiyah Covid 19 Command Center. In a sociological perspective there is a dialectic between the objective reality of Covid 19 as a real virus and must be watched out for and the subjective reality which considers that Covid 19 is an ordinary disease, the two realities form different behaviors between the Hifz Nafs principle of protecting oneself and being surrendered to the situation due to the demands of social activity. and economic needs. This public perception is formed because the Stock of Knowladge is a source of knowledge about Virus 19, humans as the host and the human environment that forms different mindsets from one another in life.